Identification of Selection Criteria for Suppliers of Raw Materials in the Supply Chain of the Kavir Steel Complex - Mohsen Ghobadi (International Journal of Supply Chain Management, 2019)
Abstract - selection of supplier is a major issue in the supply chain, so that manufacturers spend 60 percent of their time on raw materials. Implementation and components. In addition, 70% of production costs are related to the purchase of goods and services. Therefore, selecting and determining the most suitable supplier is an important issue in the supply chain. One of the problems of the Kavir Steel Industry And the purpose of this research is to solve this problem in the industry, which is possible through library studies and field study in the industry through the questionnaire .In this project, we have tried to evaluate the 20 selected components, which will determine at the end of the project what are the most important factors in the Kavir steel complex.